AGAMOUS Gene as a New Sex-Identification Marker in Fig (Ficus carica L.) Is More Efficient Than RAN1 - Wang, Xu; Song, Miaoyu; Flaishman, Moshe A.; Chen, Shangwu; Ma, Huiqin (Frontiers in Plant Science, 2021)
Fig is an ancient gynodioecious fruit tree with females for commercial fruit production and hermaphrodites (males) sometimes used as pollen providers. An early sex-identification method would improve breeding efficiency. Three AGAMOUS (AG) genes were recruited from the Ficus carica genome using AG sequences from Ficus microcarpa and Ficus hispida. FcAG was 5230 bp in length, with 7 exons and 6 introns, and a 744-bp coding sequence. The gene was present in both female and male fig genomes, with a 15-bp deletion in the 7th exon. The other two AG genes (FcAG2-Gall_Stamen and FcAG3-Gall_Stamen) were male-specific, without the 15-bp deletion (759-bp coding sequence), and were only expressed in the gall and stamen of the male fig fruit. Using the deletion as the forward primer (AG-Marker), male plants were very efficiently identified by the presence of a 146-bp PCR product. The previously reported fig male and female polymorphism gene RESPONSIVE-TO-ANTAGONIST1 (RAN1) was also cloned and compared between male and female plants. Fifteen SNPs were found in the 3015-bp protein-coding sequence. Among them, 12 SNPs were identified as having sex-differentiating capacity by checking the sequences of 27 known male and 24 known female cultivars. A RAN1-Marker of 608 bp, including 6 SNPs, was designed, and a PCR and sequencing-based method was verified with 352 fig seedlings from two hybrid populations. Our results confirmed that the newly established AG-Marker is as accurate as the RAN1-Marker, and provide new clues to understanding Ficus sex determination.